Pengaruh Pola Pemberian ASI Terhadap Perkembangan Motorik Kasar Pada Bayi Usia 6-24 Bulan Di Wilayah Kerja Puskesmas Pangkajene (Window of Public Health Journal, 2025)
Exclusive breastfeeding has several benefits, one of which is supporting gross motor development in infants. Gross motor skills are developmental skills that involve large muscles, such as when a baby turns over, walks, and jumps. The purpose of this study was to determine the effect of breastfeeding patterns on gross motor development in infants aged 6-24 months in the working area of ​​the Pangkajene Community Health Center, Sidrap Regency. The population in this study was all infants aged 6-24 months, totaling 170 infants at the Pangkajene Community Health Center. The sampling technique used was purposive sampling, and 62 infants were obtained at the Pangkajene Community Health Center. The type of research employed was an analytical observational study with a cross-sectional design. The instruments used were questionnaires and Denver II forms. The results of this study showed that 35 mothers (56.5%) practiced exclusive breastfeeding, and 27 mothers (43.5%) practiced non-exclusive breastfeeding. Of the 62 infants, 43 (69.4%) had normal gross motor development in children aged 6-24 months, while 19 (30.6%) had abnormal gross motor development. The study concluded that breastfeeding patterns influence gross motor development in infants aged 6-24 months in the Pangkajene Community Health Center, Sidrap Regency. It is recommended that mothers exclusively breastfeed their infants to support gross motor development.